(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Inclusive education demands that all learners — regardless of cognitive, linguistic, or physical diversity — have equitable access to high-quality English language instruction. The rapid proliferation of Artificial Intelligence (AI) tools in educational contexts has opened transformative possibilities for personalised, adaptive, and inclusive writing pedagogy. This paper examines how AI-powered technologies, including large language models, automated writing evaluation (AWE) systems, and multimodal feedback platforms, can be systematically integrated into English as a Foreign Language (EFL) writing instruction to support diverse learner populations. Drawing on current empirical research and pedagogical frameworks, the study analyses benefits, challenges, and ethical considerations of AI-assisted inclusive writing education. The findings suggest that when thoughtfully implemented, AI tools significantly reduce barriers for learners with diverse needs while enhancing overall writing proficiency outcomes.